Efforts to Enforce Criminal Laws in the Forestry Sector Against Cases of Destruction of Customary Forests - Sofia Jaflean; Margie Gladies Sopacua; Iqbal Taufik (TATOHI: Jurnal Ilmu Hukum, 2022)
Introduction: Forests are natural resources that provide great benefits for human welfare, both tangible benefits that are felt directly, and intangible benefits that are felt indirectly.Purposes of the Research: Reviewing and discussing Analyzing and discussing efforts to enforce criminal law in the forestry sector in the case of destruction of customary forests in the State of Sabuai. Methods of the Research: Descriptive analytical research using a normative juridical approach is formulated in the results of literature research and the obtained legal materials will be analyzed and studied in a structured research system so that the results will draw conclusions and be equipped with suggestions.Results of the Research: Indigenous peoples are very dependent on the forest, because the forest is a gift from their ancestors that must be preserved which is called the customary forest. Customary forests are forests that are in the territory of customary law communities. The definition of customary forest refers to the status of the forest area. Indigenous peoples have authority over forest areas but within the framework of state ownership. Therefore, customary law communities have customary rights over the land they occupy and own is in a forest area. In 2018 CV Sumber Berkat Makmur was designated as the holder of a Location Permit for Nutmeg Plantation Business Needs on behalf of CV Sumber Berkat Makmur located in Sabuai Village, Siwalalat District, Eastern Seram Regency. Based on the Decree, a recommendation from the Governor of Maluku was issued Number: 528/64 of 2018 dated February 1, 2018 concerning the Granting of a Location Permit for Nutmeg Plantation Business Needs on behalf of CV Sumber Berkat Makmur which is located in Sabuai Village, Siwalalat District, Eastern Seram Regency which on the basis of The Decree was issued by the Governor of Maluku Recommendation Number: 552-43 of 2018 concerning Land Suitability with the Macro Plan for Plantation Development of the Maluku Province to CV Sumber Berkat Makmur. Efforts to enforce criminal acts in the field of legal forestry against cases of destruction of customary forests in Sabuai Village, including efforts to instill customary law values in the community, optimize and prioritize criminal law enforcement against destruction of customary forests in Sabuai village, increase public awareness not to participate in regarding the destruction of customary forests in Subai Village, holding socialization related to legal rules relating to customary forests, as well as their legal consequences or consequences, and the need to establish a supervisory body for customary forests in Sabuai Village.